1993
DOI: 10.1073/pnas.90.15.7181
|View full text |Cite
|
Sign up to set email alerts
|

Hepsin, a putative cell-surface serine protease, is required for mammalian cell growth.

Abstract: Hepsin was previously identified as a putative cell-surface serine protease. When hepatoma cells were treated with anti-hepsin antibodies, their growth was substantially arrested, suggesting the requirement of hepsin molecules present at the cell surface for normal cell growth. This was further supported by a gross inhibition of cell growth with hepsinspecific antisense oligonucleotides. Upon treatment of cells with antisense oligonucleotides, rapid reduction in cellular hepsin was observed. This reduction in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
72
1
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 15 publications
(8 reference statements)
1
72
1
1
Order By: Relevance
“…Hepsin belongs to a family of trypsin-like transmembrane serine proteases [11]. We chose hepsin for gene profiling using real time RT-PCR because recent microarray and RT-PCR data showed more hepsin expression in samples of malignant human prostate than in benign tissue [12-16].…”
Section: Assessment Of Hepsin Mrna Levelsmentioning
confidence: 99%
“…Hepsin belongs to a family of trypsin-like transmembrane serine proteases [11]. We chose hepsin for gene profiling using real time RT-PCR because recent microarray and RT-PCR data showed more hepsin expression in samples of malignant human prostate than in benign tissue [12-16].…”
Section: Assessment Of Hepsin Mrna Levelsmentioning
confidence: 99%
“…[53][54][55] Hepsin, encoded by Hpn, is a type-II membrane-associated serine protease, 56 and is frequently overexpressed in several tumor cell lines, including hepatoma, mammary carcinoma, epithelioid carcinoma, and ovarian carcinomas. [57][58][59] An anti-hepsin antibody or hepsin-specific antisense oligonucleotides inhibited the growth of human hepatoma cells, indicating that hepsin was probably essential for their growth. 58 Arachidonate 12-lipoxiganase, encoded by Alox12, is a member of the lipoxygenase family and is expressed in platelets, megakaryocytes, epidermal cells, and some tumor cell lines.…”
Section: Figurementioning
confidence: 99%
“…[57][58][59] An anti-hepsin antibody or hepsin-specific antisense oligonucleotides inhibited the growth of human hepatoma cells, indicating that hepsin was probably essential for their growth. 58 Arachidonate 12-lipoxiganase, encoded by Alox12, is a member of the lipoxygenase family and is expressed in platelets, megakaryocytes, epidermal cells, and some tumor cell lines. [60][61][62][63] Overexpression of arachidonate 12-lipoxiganase in the human breast cancer cell line MCF-7 and the human prostate adenocarcinoma cell line PC3 stimulates tumor growth by inducing angiogenic activity.…”
Section: Figurementioning
confidence: 99%
“…4 Antisenseoligonucleotide blockade of hepsin affects cell growth and enlarges and flattens hepatoma cells. 5 Several in vitro studies have identified substrates for hepsin, including coagulation factor VII, 6 prohepatocyte growth factor (pro-HGF), 7 and prourokinase-type plasminogen activator. 8 In addition, hepsin colocalizes with desmoplakin at the sites of desmosomal junctions.…”
mentioning
confidence: 99%